Resolução de problemas na formação continuada e em aulas de matemática nos anos iniciais - Oliveira, Sandra Alves de (Universidade Federal de São Carlos, 2012)
This text reports a descriptive and interpretative research that analyzed challenges, dilemmas, knowledge and learning that were present in the process of continuing professional education of a group of sixteen Early Years teachers who attended an extension activity - "Mathematics in the Early Years: Program of Continuing Professional Education for Early Years Teachers from the Municipal Secretary of Education of São Carlos" - during the first semester of 2011, while studying and using the methodology of problem solving in mathematics lessons. The theoretical references that support this research are based on studies about problem solving and teacher education. The organization of the team/group that was involved in the continuing professional education activity founded the study. The continuing education program occurred in a perspective of collaborative work. Empirical data were constructed using a questionnaire, semi-structured interviews, audio and video records, written material, a reflective field journal elaborated by the participating teachers and the researcher, who worked as a trainer and observed the actions of the teachers in mathematics lessons. The data analysis indicates that the collaborative work approach helped the teachers to review knowledge and concepts about problem solving in mathematics lessons and implement more meaningful practices in their classes. The activities that were developed and created in the continuing education program gave the necessary contribution so that the sixteen participating teachers had the possibility to use, in their mathematics classes in Early Years education, the methodology of problem solving according to the perspective of Van de Walle, Onuchic, Vila and Callejo. The process of training was important because it valued the teaching knowledge and learning and enabled the teachers to build and rebuild other ones, express their experiences, their feelings about their practices and their interest in the development of problem solving methodology in teaching and learning of mathematics in the Early Years; understand the theoretical and practical knowledge in teaching and learning of mathematics and/or give them a new meaning. This knowledge contributed for the practical application of problem solving methodology in mathematics classes in Early Years Education.
Keywords: Educação matemática; Resolução de problemas; Saberes docentes; Professores - formação; Trabalho colaborativo; Problem solving methodology; Teaching knowledge and learning; Mathematics training of polyvalent teachers; Collaborative work; CIENCIAS HUMANAS::EDUCACAO